2010
DOI: 10.4049/jimmunol.0903740
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Induce Regulatory T Cell Proliferation through Antigen-Dependent and -Independent Interactions

Abstract: Material Supplementary 0.DC1http://www.jimmunol.org/content/suppl/2010/08/04/jimmunol.090374

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 42 publications
7
81
0
1
Order By: Relevance
“…Although specific antigen-dependent interactions do not appear to be required to mediate DC immunoregulatory functions [36,37], our data indicate that in vitro DC antigen specification can target diabetogenic T cells and convey tolerogenic signals. Indeed, it has been shown that antigenprimed DCs induce better protection in NOD mice and that cognate antigen-MCH class II complexes enhance IL-2 induced Treg proliferation [37][38][39].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although specific antigen-dependent interactions do not appear to be required to mediate DC immunoregulatory functions [36,37], our data indicate that in vitro DC antigen specification can target diabetogenic T cells and convey tolerogenic signals. Indeed, it has been shown that antigenprimed DCs induce better protection in NOD mice and that cognate antigen-MCH class II complexes enhance IL-2 induced Treg proliferation [37][38][39].…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, it has been shown that antigenprimed DCs induce better protection in NOD mice and that cognate antigen-MCH class II complexes enhance IL-2 induced Treg proliferation [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that DCs are crucial for the induction of T regs and that the extent of T reg induction is determined by the maturation state of the DCs (27,29,30,75). Thus, Banerjee et al showed that CC-DCs are capable of high T reg induction (up to 10% Foxp3 + CD4 + T cells) (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…Once migration is achieved, smDC have been shown to mediate auto-and alloimmune tolerance by the preferential expansion of Ag-specific IL-2-dependent CD4 + CD25 + Foxp3 + Treg cells (8,(15)(16)(17)(18). In fact, in the context of a tolerizing DC phenotype, an intact IL-2 activation pathway has been shown to be essential for Treg differentiation (19,20). In addition to the prototypical CD4 + CD25 + Foxp3 + phenotype, Foxp3 appears to drive CD39 expression, an ectonucleotidase that hydrolyzes extracellular ATP and whose catalytic activity is strongly enhanced by TCR ligation; CD39 expression has been shown to be specifically relevant to Treg protection in the context of transplantation immunology (21).…”
Section: Endritic Cells (Dc) Undergo Transition From Immature DCmentioning
confidence: 99%